The economic crisis in 1997 has caused the rupiah exchange rate to depreciate from about Rp 2,500/US dollar to Rp 15,000/US dollar in the time of crisis and to around Rp 9,300/US dollar recently. This condition caused the authority to focus their policy in stabilizing rupiah and reducing inflation rate. The objectives of this research are firstly, to analyze the response of the variables of industrial production index (IPI), money supply and interest rate when the shocks to exchange rate and - M. Ilham Riyadh; Rina Oktaviani; Hermanto Siregar (Forum Pasca Sarjana, 2009)
The economic crisis in 1997 has caused the rupiah exchange rate to depreciate from about Rp 2,500/US dollar to Rp 15,000/US dollar in the time of crisis and to around Rp 9,300/US dollar recently. This condition caused the authority to focus their policy in stabilizing rupiah and reducing inflation rate. The objectives of this research are firstly, to analyze the response of the variables of industrial production index (IPI), money supply and interest rate when the shocks to exchange rate and inflation take place; secondly, to analyze the contributions of IPI, inflation rate, money supply and interest rate differentiation in explaining the variation of exchange rate and inflation rate of Indonesia; and thirdly, to formulate the monetary policy of implication stabilizing the rupiah and inflation rate. The results show that the shock to the rupiah exchange rate has resulted in a very high depreciation responded by an increase in money supply and price but IPI decreases. To reduce depreciation, authority can increase the interest rate. Meanwhile the shock to inflation are responded directly by increases in Bank Indonesia certificate rate so that the money supply decreases, exchange rate appreciates, and IPI decreases. To stabilize the rupiah exchange rate and the inflation rate, monetary authority should carry out the tight money policy through a relatively high interest rate, so capital inflow will take place. Key words: monetary policy, rupiah exchange rate, inflation rate, industrial production index, vector autoregressive